Screening of Some Exotic Rice Germplasm Against Brown Spot (Bipolaris oryzae) Disease under Rainfed Conditions: Short Communication: Brown Spot Discase Resistance in Rice - Yaqoob, Muhammad (Biological Sciences - PJSIR, 2015)
Ten different lines including one approved variety and one susceptible check were tested against brown spot disease of rice under low water application conditions. The disease data were recorded on 1-9 rating scale. The results revealed highly significant differences among various rice genotypes against disease reaction ranging from highly resistant to highly susceptible in different genotypes. Three lines remained highly resistant, four resistant and two moderately resistant under rainfed conditions.